2014
DOI: 10.4172/2165-7904.1000224
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is a Risk Factor for Renal Toxicity and Wound Complications among a Cohort of Pediatric Cancer Patients at a Single Tertiary Care Institution

Abstract: Background: Evidence exists in the adult literature linking obesity to an elevated risk for the development of certain malignancies, and to an increase in treatment-related complications. Little information is available examining this relationship in the obese pediatric oncology population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The vitamin D deficiency is actually responsible for the cardiovascular diseases. The obesity is also a risk factor of renal toxicity and wound complications [36]. A research was conducted on the adult's population of Living in Nigeria's Largest Urban City to calculate the prevalence of coronary heart diseases risk factors and the authors suggested that high lipid profile, physical inactivity, high blood pressure, tobacco smoking, diabetes and obesity are the risk factors of coronary heart diseases in Nigerian population [37].…”
Section: Interaction Between Nutrition Obesity and The Immune Systemmentioning
confidence: 99%
“…The vitamin D deficiency is actually responsible for the cardiovascular diseases. The obesity is also a risk factor of renal toxicity and wound complications [36]. A research was conducted on the adult's population of Living in Nigeria's Largest Urban City to calculate the prevalence of coronary heart diseases risk factors and the authors suggested that high lipid profile, physical inactivity, high blood pressure, tobacco smoking, diabetes and obesity are the risk factors of coronary heart diseases in Nigerian population [37].…”
Section: Interaction Between Nutrition Obesity and The Immune Systemmentioning
confidence: 99%